Pre-Service Teachers’ Performance in Applying the ARCS Model on Technology in Education Course - Suji Rahmawati; Didik Sucahyo; Yuni Utami Asih (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2024)
This study aimed to find: (1) to elaborate pre-service teachers’ performance in applying the ARCS model on technology in education course; (2) to elaborate pre-service teachers’ difficulties and solution in integrating ARCS to technology in education. The Attention, Relevance, Confidence, Satisfaction (ARCS) model is an instructional design framework developed by Keller (2010), the model focuses on strategies to motivate and engage learners in the educational process. This study used a case study with qualitative approach. In this study, the participants were three student-teachers of English Education Department at who met the criteria. The data of this research were collected through interviews and analyzed by using Thematic Analysis adopted from Braun & Clarke (2006). The researcher found that the pre-service teachers in the Technology in Education course relatively had good knowledge of ARCS components. It was concluded that most of the pre-service teachers were able to integrate the core components of ARCS. Some of The EFL pre-service teachers taught their content lesson effectively by using ARCS instructional models with specific technology strategies. The result also showed that various difficulties were faced by the pre-service teachers in integrating ARCS to Technology in Education course. The difficulties were from designing the content, translating the material to media, choosing the suitable template, making the material relevance, and set learning objective. To overcome the difficulties, the pre-service teachers looked for the example, making the outline, and also making careful planning in translating the material.